2015
DOI: 10.1016/j.amjcard.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Ischemia in Adults Secondary to Missed Kawasaki Disease in Childhood

Abstract: Coronary artery aneurysms that occur in 25% of untreated Kawasaki disease (KD) patients may remain clinically silent for decades and then thrombose resulting in myocardial infarction. Although KD is now the most common cause of acquired heart disease in children in Asia, the United States, and Western Europe, the incidence of KD in Egypt is unknown. We tested the hypothesis that young adults in Egypt presenting with acute myocardial ischemia may have coronary artery lesions due Kawasaki disease (KD) in childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Catheter intervention is now established as a first-line therapeutic strategy for adult patients with coronary artery disease, and has provided satisfactory therapeutic results [6]. However, in adult as well as pediatric patients with KD, limited experience with catheter interventions has been reported [4,7,8]. Options for coronary revascularization in KD generally consist of intravenous coronary thrombolysis, percutaneous coronary intervention, or coronary artery bypass grafting [9,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Catheter intervention is now established as a first-line therapeutic strategy for adult patients with coronary artery disease, and has provided satisfactory therapeutic results [6]. However, in adult as well as pediatric patients with KD, limited experience with catheter interventions has been reported [4,7,8]. Options for coronary revascularization in KD generally consist of intravenous coronary thrombolysis, percutaneous coronary intervention, or coronary artery bypass grafting [9,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication from Egypt, Rizk et al have reported that 6.7 % of adults less than 40 y of age who had possible myocardial ischemia had angiographic lesions which suggested antecedent KD [32]. It has been suggested that even children who do not have overt CAA on echocardiography need long-term follow-up with CT calcium scoring [33].…”
Section: Is Kawasaki Disease a Disease Of Public Health Importance Fomentioning
confidence: 99%
“…The commonest signs were fever, rash, oral changes, and conjunctivitis [ 18 ••]. A study from Egypt reported that 6.7% of adults aged 40 years or younger and who underwent angiography for evaluation of possible myocardial ischemia had lesions consistent with antecedent KD [ 19 ]. A Congolese study reported on a case series of 11 patients with KD seen between 2003 and 2014, of which nine of these cases were classified as complete Kawasaki disease.…”
Section: Medium-vessel Vasculitismentioning
confidence: 99%